2007
DOI: 10.1095/biolreprod.107.060632
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells: Key to Fetal Tolerance?1

Abstract: Pregnancy is a unique event in which a fetus, despite being genetically and immunologically different from the mother (a hemi-allograft), develops in the uterus. Successful pregnancy implies avoidance of rejection by the maternal immune system. Fetal and maternal immune cells come into direct contact at the decidua, which is a highly specialized mucous membrane that plays a key role in fetal tolerance. Uterine dendritic cells (DC) within the decidua have been implicated in pregnancy maintenance. DC serve as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 98 publications
3
139
0
4
Order By: Relevance
“…54 DCs are considered to be the immune 'guardians' in the uterine-mucosa, capable of inducing tolerance under normal physiological conditions. 55 DCs in the decidua produce less IL-12 than do peripheral blood DCs, and decidual myeloid DCs induce a higher percentage of T-helper type 2 (Th2) lymphocytes than do peripheral blood DCs.…”
Section: Recruitment Of Antigen-presenting Cells (Macrophages and Dcs)mentioning
confidence: 99%
“…54 DCs are considered to be the immune 'guardians' in the uterine-mucosa, capable of inducing tolerance under normal physiological conditions. 55 DCs in the decidua produce less IL-12 than do peripheral blood DCs, and decidual myeloid DCs induce a higher percentage of T-helper type 2 (Th2) lymphocytes than do peripheral blood DCs.…”
Section: Recruitment Of Antigen-presenting Cells (Macrophages and Dcs)mentioning
confidence: 99%
“…The encounter of seminal fluid with maternal DCs present either in vaginal lumen or in endometrial tissue at the time of mating 25 represents therefore the first event leading to a protective adaptive immune response. It has been proved that uterine DCs are rather tolerogenic DCs than mature DCs 26 and Heme Oxygenase-1 (HO-1) seems to be pivotal in maintaining maternal DCs in an immature state, which contributes to the expansion of the peripheral Treg population. 27 Not only does the seminal fluid provide the antigens to be presented to APCs but also recruits Treg into the uterus or drives their expansion and the draining lymph nodes as demonstrated by the lack of expansion of Treg after in females mated with males without seminal vesicles but not with vasectomized males 19 Much attention was focused in the production of cytokines by CD4 T helper cells particularly after Piccinni and colleagues showed that decidual T cells from women with unexplained recurrent abortions produced abnormally low Leukemia inhibtory factor (LIF), IL-4, and IL-10 levels.…”
Section: Tafurimentioning
confidence: 99%
“…in the events underpinning successful embryo implantation and establishment of pregnancy, through their roles in decidual tissue remodeling and angiogenesis, and in the induction of maternal-fetal tolerance (1,2). This has led to a focus on identifying the factors that regulate DCs in the uterine endometrium, since deficiency in these cells is implicated in forms of infertility where the endometrium is not receptive to implanting embryos, or in preeclampsia where immune tolerance of the placenta is insufficient (3)(4)(5).…”
Section: Endritic Cells (Dcs) Have Emerged As a Critical Cell Lineagementioning
confidence: 99%